A rare occurrence: A case report on alobar holoprosencephaly with cyclopia - Sharma, Bandana; Malviya, Himani; Malik, Anchal; Ray, Rahul (Indian Journal of Case Reports, 2024)
Alobar holoprosencephaly with cyclopia is a rare lethal congenital anomaly frequently accompanied by other malformations and characterized by large variations in incidence. Alobar holoprosencephaly presents as a congenital brain malformation characterized by the incomplete separation of the brain hemispheres during fetal development, typically occurring between the 4th and 6th gestational weeks, affecting about 1 in 250 conceptuses and 1 in 16,000 live births. This anomaly involves the failure of transverse cleavage into the diencephalon and telencephalon and is often accompanied by various midline facial abnormalities. In this report, we detail a case of a patient diagnosed prenatally with alobar holoprosencephaly with cyclopia, which is a rare, severe craniofacial abnormality encountered in approximately 1 in 100,000 births. Due to the severity of the condition, the decision was made to induce labor, resulting in the delivery of a stillborn baby. Despite the grim prognosis associated with this condition, we emphasize the importance of comprehensive prenatal counseling and support for families navigating such complex medical circumstances. Through this report, we aim to contribute to the understanding and compassionate care of individuals affected by alobar holoprosencephaly with cyclopia.